The floating circus - Zimmer, Tracie Vaughn (New York : Bloomsbury Children's Books : Distributed to the trade by Macmillan, 2008)
In 1850s Pittsburgh, Owen leaves his younger brother and sneaks aboard a circus housed in a riverboat, where he befriends a freed slave, learns to work with elephants, and comes to terms with the choices he has made in his life.
850
Keywords: Abandoned children -- Fiction; Circus -- Fiction; River boats -- Fiction